Brazil holds all-electronic national election. - Riebeek, H. (IEEE spectrum)
On 6th October 2002, in Brazils first completely electronic national election-and the worlds largest so far-more than 115 million Brazilians used them to vote for president, state governors, and legislators. The election itself inspired some turmoil. Stock markets across the world fell in anticipation of a leftist Brazilian government getting elected-a first for this South American nation. Thousands of troops patrolled the country during the election, but the machines worked very well. Since electronic voting is not so new to Brazil, people knew how to use the machines. The country's approximately 405000 voting machines were provided mainly by National Semiconductor Corp. They run on the Microsoft Windows CE operating system and software from another partner in the venture, Unisys Corp. Each machine has an integrated LCD screen and a numeric keyboard that resembles a telephone keypad The machine displays serially a photo of each candidate and a number beside his or her name and party affiliation. Voters select preferred candidates keying in the numbers assigned to each. Votes are recorded in flash memory and transferred to a floppy disk. At the end of the election, officials bring the encrypted disks to regional electoral tribunals, which transmit results via dialup links to Brasilia, the nation's capital. A hard copy of each vote is also recorded on an internal printer locked inside the machine.